A genoserotyping system for a fast and objective identification of Salmonella serotypes commonly isolated from poultry and pork food sectors in Belgium. (October 2020) - Gand, Mathieu; Mattheus, Wesley; Roosens, Nancy; Dierick, Katelijne; Marchal, Kathleen; Bertrand, Sophie; De Keersmaecker, Sigrid C.J.
Abstract: Humans are mostly contaminated by Salmonella through the consumption of pork- and poultry-derived food products. Therefore, a strict monitoring of Salmonella serotypes in food-producing animals is needed to limit the transmission of the pathogen to humans. Additionally, Salmonella can lead to economic loss in the food sector. Previously, a genoserotyping method using the MOL-PCR and Luminex technology was developed for the identification of the 6 Salmonella serotypes, and their variants, subjected to an official control in the Belgian food sector. In this study, 3 additional assays using the same technology were developed for the rapid and cost-effective detection of 13 dangerous highly invasive serotypes or other serotypes frequently isolated from the Belgian poultry and pork sector, i.e. Agona, Anatum, Brandenburg, Choleraesuis, Derby, Enteritidis vaccine strains, Gallinarum var. Gallinarum/Pullorum, Livingstone, Mbandaka, Minnesota, Ohio, Rissen and Senftenberg. Moreover, the previously developed first MOL-PCR assay was improved for S. Paratyphi B and serogroup O:3 detection. Finally, a Decision Support System hosted by a web application was created for an automatic and objective interpretation of the Luminex raw data. The 3 new assays and the modifications of the first assay were validated with a 100% accuracy, using 553 Salmonella and non- Salmonella strains in total. Highlights: Classical Salmonella serotyping is expensive, time-consuming and subjective. 3 new MOL-PCR & Luminex assays developed for accurate Salmonella genoserotyping. A Decision Support System performs the automatic interpretation of the raw data. Validation of the method with 553 Salmonella and non- Salmonella strains. Fast and cost-effective identification of Salmonella serotypes from the food sector.